NEGOSIASI NILAI TRADISIONAL DAN KESETARAAN GENDER STRATEGI PENDIDIKAN ISLAM DALAM MEMBANGUN KULTUR MADRASAH YANG INKLUSIF DAN BERKEADILAN - Nila Hanif Ulfiana; Ahmad Rafi Fitroh; Ainur Rofiq (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze Islamic educational strategies for negotiating traditional values ​​and gender equality principles to foster an inclusive and equitable madrasah culture. Employing a qualitative case study approach, the research focuses on educational practices, institutional policies, and *madrasah* culture regarding the integration of Islamic values ​​and gender equality. Data were gathered through in-depth interviews with *madrasah* principals, teachers, students, and parents, supplemented by participant observation and document analysis. Data analysis utilized an interactive model involving data condensation, data display, and conclusion drawing and verification. Data validity was ensured through the triangulation of sources, methods, and theories. The findings reveal that the negotiation between traditional values ​​and gender equality is realized through the contextual and moderate reinterpretation of Islamic values, gender-responsive leadership, inclusive curriculum development, and the cultivation of a school culture that values ​​equal participation and opportunity. These strategies create an educational environment that remains rooted in Islamic tradition while aligning with principles of social justice. The study’s novelty lies in its integrative analysis of how Islamic education harmonizes traditional values ​​with gender equality—through the reinterpretation of teachings, leadership, curriculum, and culture—thereby reinforcing the madrasah's role as an agent of social transformation grounded in the principle of rahmatan lil ‘alamin (mercy to all creation).